Hemorheology and exercise: effects of warm environments and potential consequences for sickle cell trait carriers - Connes, P. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The relationship between blood rheology and hemodynamics is complex, and the following review presents several aspects of exercise hemorheology, with the focus on both cycling and running as exercise. The scientific literature assessing the effects of warm environment on exercise hemorheology is presented and the potential consequences for a specific population, sickle cell trait carriers, are discussed.